Melancolía en los relatos de mercado de Nadia Prado - Molina, Cristian Julio (Revista Chilena de Literatura, 2014)
The article describes the relationships between literature and the symbolic market in the context of globalization in Nadia Prado’s Job and © Copyright. The discussion advances the idea that these relations are organized around a melancholic regime that redefines them. The “regime” category reintroduces the studies of Roger Chartier in Escribir las prácticas, specifically when he points out that this foucauldian notion refers to the articulation of discourse and the practices in which it takes place.